Recent large-scale mixed layer and vertical stratification maxima changes - Roch, Marisa; Brandt, Peter; Schmidtko, Sunke (Frontiers in Marine Science, 2023)
The warming climate is causing a strengthening of ocean stratification. Ocean stratification, in turn, has significant impacts on physical, biogeochemical and ecological processes, such as ocean circulation, ventilation, air-sea interactions, nutrient fluxes, primary productivity and fisheries. How these processes are affected in detail by changing stratification still remains uncertain and are likely to vary locally. Here, we investigate the state and trend of different parameters characterizing the stratification of the global upper-ocean which can be derived from Argo profiles for the period 2006-2021. Among those parameters are mixed layer depth, magnitude and depth of the vertical stratification maximum. The summertime stratification maximum has increased in both hemispheres, respectively. During wintertime, the stratification maximum has intensified in the Northern Hemisphere, while changes in the Southern Hemisphere have been relatively small. Comparisons to mixed layer characteristics show that a strengthening stratification is mainly accompanied by a warming and freshening of the mixed layer. In agreement with previous observational studies, we find a large-scale mixed layer deepening that regionally contributes to the increasing stratification. Globally, the vertical stratification maximum strengthens by 7-8% and the mixed layer deepens by 4 m during 2006-2021. This hints to an ongoing de-coupling of the surface ocean from the ocean interior. The investigated changes can help determine the origin of existing model-observation discrepancies and improve predictions on climate change impact on upper-ocean ecology and biogeochemistry.